Assessment of Multicausal Factor related Stunting at Limited Resources Area, Indonesia: A case study in Nias Island, Indonesia - Tri Bayu Purnama; Rapotan Hasibuan; Nofi Susanti; Yulia Khairina Ashar; Moch Thoriq Assegaf; Arrafi Insani (Social Medicine Publication Group, 2023)
The problem of stunting is still threatening the health of children worldwide and the problem of stunting will be greater in underdeveloped areas. This study aims to map the multi-casual factor of stunting in a resource-limited area of ​​Nias. This study was located on Nias Island, North Sumatera Province, Indonesia which is categorized as a remote area then collected data from the Indonesian Basic Health Survey in 2018. Treemap was used to map environment, behavior, access to health care, and infectious diseases among children less than 5 years old. The highest prevalence of severe stunting in infants aged less than 2 years on Nias Island in 2018, respectively, were Nias District (35.9%), North Nias (28.6%), South Nias (21.8%), GunungSitoli (17.9%) and West Nias (12.31%) and the highest prevalence of severe stunting among infants less than five years old was Nias Districts (35.81%). The impact of difficult access to health services can affect the monitoring of health services for infants and mothers. This can be seen from the high prevalence of diseases in children under five such as diarrhea, ARI, and pneumonia. In Nias Districts, the prevalence of diarrhea, pneumonia, and ARI were 13.67%, 13.73%, and 13.07% respectively. The highest incidence of ARI and diarrhea was recorded in South Nias Districts with a prevalence of 27.52% and 21.64% respectively.